Oceanographic Parameter Measurement System Based on LoRA Communication Module - Amir, Ashadi; Suwardoyo, Untung; Pratami Irwan, Irninthya Nanda (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2024)
Measurement of oceanographic parameters is needed to determine the condition of the ecosystem in the water area so that it can be the basis for carrying out conservation activities in marine waters. Measurement of physical and chemical parameters used manually which causes the data obtained is still susceptible to observational errors. In this study, a system was designed that can measure oceanographic parameters periodically. The designed system consists of a temperature sensor, turbidity sensor, pH sensor and TDS sensor integrated with a microcontroller device. The system consists of two main parts, a sensor node that has a function as a transmitter and a gateway that has a function as a receiver. Initial testing is done by calibrating and validating data for each sensor used. The next test was carried out by testing the transmission of data from the measurement of oceanographic parameters in the form of water pH, salinity, water temperature and water turbidity from the sensor node to the gateway using the LoRA Ebyte E220 communication module. The test results show that the sensor node measurement data can be sent to the gateway by setting the distance between devices as far as 500 meters. The resulting data transmission delay is in the range of 2-10 seconds